Endoscopic treatments of advanced esophageal cancer and other esophagocardial strictures: Review of 54 personal cases - Piazze, Alvaro (Cirugía del Uruguay, 2005)
Advanced esophagea/ cancer (AEC) is diagnosed during those stages in which surgery is posible, it is pal/iative for disphagia, with high morbimortality. In inoperable or irresectable cases, resorting to alternative treatment such as radiotheraPY or endoscopy may pal/iate disphagia. Endoscopically it is possib/e to place a transtumoral nasogastric catheter (NGC) for preoperative nutrition or branchial therapy (intratumoral iridium). lt is possible to dilate the tumor and place and indwelling p/astic or auto expandable prosthesis or to inject abso/ute intratumoral alcohol. There is an evaluation of resu/ts and morbimortality of personal case material through the retrospective study of 54 patients in whom 120 procedures such as those referred to above were carried out.